The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jbm.a.30824
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of UHMWPE wear particles down to ten nanometers in size from in vitro hip and knee joint simulators

Abstract: There is currently considerable interest in the wear debris and osteolytic potential of different types of bearings used in total joint replacements. The biological activity of the wear debris is dependent on the size and volume of the particles produced. Wear volume also plays an important role in the functional biological activity of a joint replacement. In vitro studies have shown that crosslinking of ultra high molecular weight polyethylene (UHMWPE) acetabular cups and tibial trays produces a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 30 publications
5
61
0
1
Order By: Relevance
“…With the introduction of improved wear resistant materials (like highly cross-linked UHMWPE) to fabricate total joint components, there has been a decrease in wear debris volume, but has led to increased generation of nano-debris 32 . Although a well corroborated mechanism as to how cells respond to nano-wear-debris is presently elusive, even these smaller nano-size particles (like their larger counterparts) are phagocytosed by cells prior to eliciting a biological response.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of improved wear resistant materials (like highly cross-linked UHMWPE) to fabricate total joint components, there has been a decrease in wear debris volume, but has led to increased generation of nano-debris 32 . Although a well corroborated mechanism as to how cells respond to nano-wear-debris is presently elusive, even these smaller nano-size particles (like their larger counterparts) are phagocytosed by cells prior to eliciting a biological response.…”
Section: Discussionmentioning
confidence: 99%
“…Although strong correlations between wear rates and osteolysis were reported in a literature review [11], such findings could be expected, as smaller particle volumes are released into the periprosthetic tissue triggering less cytotoxic response. However, a cell culture study [38] suggested wear particles of cross-linked PE can be smaller and shaped differently from those of alternative PE and thus may have a higher cytotoxicity (functional osteolytic potential). As a result, cross-linked PE may produce equal or higher levels of osteolysis despite reduced wear volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The average size of crosslinked PE is reported to be smaller than conventional PE [40,47]. Combined with the reduced volume, this poses new challenges in purification, isolation, and characterization of nanometer-sized particles because even a small loss of particles through the digestion process or overestimation of size due to artifactual clumping can greatly skew the size distribution and morphologic analysis.…”
Section: Introductionmentioning
confidence: 99%